Integrating the management of critical illness with palliative care: Public health implications - Saurabh RamBihariLal Shrivastava; Prateek Sudhakar Bobhate; Anup Mukund Marar (Journal of Pediatric Critical Care)
Critical illnesses encompass a wide range of serious and life-threatening conditions that often require intensive care, including advanced life support, complex procedures, and prolonged stays in healthcare facilities. Palliative care has been acknowledged as an integral component of critical illness management by complementing curative modes of treatment. The objectives of the current article are to explore the significance of palliative care as an integral domain of the management of critical illnesses, identify the gaps in the integration of palliative care and critical illness, and propose targeted interventions to facilitate this integration. Despite the multiple benefits attributed to palliative care and its role in critical illness management, their integration has not been as expected due to the presence of multiple challenges. The combined delivery of integrated palliative care and critical illness care becomes crucial in improving patient outcomes by improving the management of symptoms.